Comparative Study of Endothelial Cell Loss after Phacoemulsification by Using 2% Hydroxypropyl Methylcellulose (HPMC) Versus 2.3% Sodium Hyaluronate (Healon 5) - Z.A Qazi, Muhammad Younis Tahir, Rafay Amin Baig, Khalid Masood Ashraf, Moazam babar (Pakistan Journal of Ophthalmology, 2008)
Purpose: To compare the protective effect of Healon 5 and HPMC on corneal endothelium during phacoemulsification. Material and Methods: All eyes scheduled to have phacoemulsification surgery by single surgeon at same centre were selected. First group was operated while using HPMC as viscoelastic agent and second group of eyes underwent identical surgery while using Healon 5 as viscoelastic agent. Patients were followed up at 24 hours, one week, one month, and 3 months after surgery for corneal endothelial cell loss by using specular microscope. Results: Fifty eyes underwent surgery equally divided in two groups. In first group HPMC was used. The mean loss of corneal endothelial cells at 3 months was 8.67 %( 6.57%-13.61%). In second group Healon 5 was used during surgery and the mean loss of corneal endothelial cells at 3 months was 8.05 %( 6.58%-10.94%). Conclusions: The rate of corneal endothelial cell loss in patients undergoing phacoemulsification cataract surgery with HPMC or Healon 5 does not vary much although Healon 5 works better if there is advanced nuclear sclerosis. But in routine cases use of HPMC is a safe and cost effective.